PENGUNGKAPAN EMISI KARBON DAN GREEN ACCOUNTING TERHADAP PERFORMA PERUSAHAAN DENGAN PENGUNGKAPAN SDGs SEBAGAI VARIABEL PEMEDIASI - Pratiwi, Laras; Somantri, Yeni Fitriani; Rahayu, Intan (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
The disclosure of carbon emissions and the application of Green Accounting in corporate sustainability reports is voluntary. This means that companies have the freedom to disclose the extent of their role in environmental sustainability. This study aims to determine the effect of carbon emission disclosure and Green Accounting on company performance with the SDGS variable as a mediator. The sampling technique uses purposive sampling, which consists of 21 companies. The results of the data analysis concluded that the companies with the highest carbon emissions are companies in the infrastructure sector, the companies that incur the highest environmental costs are companies in the energy sector, carbon emissions disclosure has no effect on company performance, carbon emissions disclosure has no effect on SDGs disclosure, Green Accounting is having a significant impact on company performance, Green Accounting has a significant effect on SDGs disclosure, SDGs have a significant effect on company performance, SDGs are unable to mediate the impact of Green Accounting on company performance, and SDGs are unable to mediate the effect of carbon disclosure on company performance. The results of this study prove that the highest carbon-producing company does not automatically become the most responsible company for environmental management. This study has important implications for companies, the government, and investors in Indonesia. Companies are advised to implement Green Accounting and SDG disclosure as part of a long-term sustainability strategy to improve their financial performance and corporate image. To encourage businesses to be more environmentally friendly, the government needs to make rules and rewards stricter when it comes to lowering carbon emissions. We advise investors to weigh SDG disclosure alongside short-term financial performance when assessing a company's long-term performance.